2018
DOI: 10.1039/c8nr04277b
|View full text |Cite
|
Sign up to set email alerts
|

New opportunities for efficient N2 fixation by nanosheet photocatalysts

Abstract: Catalytic ammonia synthesis from dinitrogen (N2) under mild conditions has been considered to be the "holy grail" of N2 fixation, which is one of the most important chemical processes in the agriculture, biological and industrial fields. Given that current artificial N2 fixation is still dominated by the energy-intensive Haber-Bosch process, solar N2 fixation represents an encouraging and fascinating route for carbon-free and energy-saving N2 fixation. However, its practical application is seriously hampered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 37 publications
1
74
0
Order By: Relevance
“…Recently, defect engineering in semiconductor photocatalysts has attracted attention as a means of providing abundant active sites for optimizing reactant (e.g., N 2 and H 2 O) adsorption and lowering activation energy barriers for challenging chemical transformations . Recently, it was demonstrated that ultrathin CuCr‐layered double hydroxides (LDHs) nanosheets containing abundant oxygen vacancies (V O ) exhibited outstanding N 2 reduction activities at wavelengths up to 500 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, defect engineering in semiconductor photocatalysts has attracted attention as a means of providing abundant active sites for optimizing reactant (e.g., N 2 and H 2 O) adsorption and lowering activation energy barriers for challenging chemical transformations . Recently, it was demonstrated that ultrathin CuCr‐layered double hydroxides (LDHs) nanosheets containing abundant oxygen vacancies (V O ) exhibited outstanding N 2 reduction activities at wavelengths up to 500 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In Table 2 , we summarize the performance of recently published photoelectrocatalysts for NRR. Comprehensive discussions of photocatalytic N 2 reduction can be found elsewhere, and are beyond the scope of this article.…”
Section: Advanced Catalysts For Nitrogen Conversion To Ammoniamentioning
confidence: 99%
“…Photochemical systems are considered to be clean and renewable due to the use of light, potentially solar, as the energy source. The detailed discussion of progress in molecular NRR catalysts and photochemical NRR can be found elsewhere . Compared with electrochemical systems, photochemical systems are not as efficient because only a portion of photons with particular wavelengths can participate in the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports indicate that 2D semiconductors are potential candidates for photocatalytic nitrogen fixation . Recently, Wang and coworkers adopted Au nanocrystal modified ultrathin 2D TiO 2 nanosheets with abundant oxygen vacancies for nitrogen fixation.…”
Section: Energy and Environment Applicationsmentioning
confidence: 99%